Negative modulation of the GABAAρ1 receptor function by histamine - Beltrán González, Andrea Natalia (2023)
Besides its function as a local mediator of the immune response, histamine can play a role as a neurotransmitter and neuromodulator. Histamine actions are classically mediated through four different G protein-coupled receptor subtypes but non-classical actions were also described, including effects on many ligand-gated ion channels. Previous evidence indicated that histamine acts as a positive modulator on diverse GABAA receptor subtypes, such as GABAAα1β2γ2, GABAAα2β3γ2, GABAAα3β3γ2, GABAAα4β3γ2 and GABAAα5β3γ2. Meanwhile, its effects on GABAAρ1 receptors, known to stand for tonic currents in retinal neurons, had not been examined before. The effects of histamine on the function of human homomeric GABAAρ1 receptors were studied here, using heterologous expression in Xenopus laevis oocytes followed by the electrophysiological recording of GABA-evoked Cl− currents. Histamine inhibited GABAAρ1 receptor-mediated responses. Effects were reversible, independent of the membrane potential, and strongly dependent on both histamine and GABA concentration. A rightward parallel shift in the concentration-response curve for GABA was observed in the presence of histamine, without substantial change in the maximal response or the Hill coefficient. Results were compatible with a competitive antagonism of histamine on the GABAAρ1 receptors. This is the first report of inhibitory actions exerted by histamine on an ionotropic GABA receptor.